The clinical efficacy and mechanism of gamma frequency electroacupuncture stimulation on the rehabilitation of upper limb motor function in stroke patients: study protocol of a randomized clinical trial - Tian, Xiaoyu; Yu, Xiaoming; Ma, Hongli; Lai, Minghui; Wu, Ruiren; Zhang, Xinglin; Zhang, Jingjing; Luo, Zifan; Fu, Wang; Feng, Wei; Hu, Jun; Shan, Chunlei; et al. (Frontiers in Neurology, 2025)
BackgroundThe field of neuroscience has discovered that gamma oscillations (30–100 Hz) in the brain play a key role in neuroplasticity, information conduction and neuroprotective mechanisms. Electroacupuncture stimulation (ES) is a modern treatment method that combines the advantages of Chinese acupuncture with those of electrical stimulation, and is widely used in the field of stroke rehabilitation. At present, there is a lack of research on the clinical efficacy and mechanism of applying gamma frequency (40-Hz) ES, a new neuromodulation mode of integrated Chinese and Western medicine, to induce gamma oscillations and promote the rehabilitation of upper limb motor function in stroke patients.Methods and analysisThis trial uses a randomized, double-blind and controlled method to evaluate the effect of 40-Hz ES of LI11 (Quchi) acupoint on upper limb motor functional rehabilitation in stroke patients. Based on this new rehabilitation program combining Traditional Chinese medicine with modern technique, all patients will receive baseline assessment, 1-week post-intervention assessment and 2-week post-intervention assessment. The primary outcomes are the Fugl-Meyer Assessment Upper Extremity Scale. The secondary indicators include electroencephalogram, National Institutes of Health Stroke Scale, Mini-mental State Examination and Modified Barthel Index.DiscussionThis trial offers novel perspectives on the application of 40-Hz electroacupuncture stimulation in neural oscillation regulation and the effectiveness of this clinically widespread technique in treating upper extremity dysfunction after a stroke and improving patients’ quality of life. The results of this study will contribute to the scientific community’s understanding of the potential mechanisms of this novel neuromodulation method, including changes in neural network connectivity, and improve existing clinical treatments to benefit more stroke patients.Clinical trial registrationhttps://www.chictr.org.cn/showprojEN.html?proj=217786, identifier ChiCTR2400082208.